2018
DOI: 10.1002/14651858.cd009115.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Phonics training for English-speaking poor readers

Abstract: Analysis 1.2. Comparison 1 Phonics training versus control (random-e ects model), Outcome 2 Non-word reading accuracy...... Analysis 1.3. Comparison 1 Phonics training versus control (random-e ects model), Outcome 3 Irregular word reading accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 89 publications
2
29
0
2
Order By: Relevance
“…At T3, when Group 2 had received systematized phonics, they outperformed Group 1 in a comparable manner. This is in line with previous studies reporting positive reading outcomes for intervention methods with a primary focus on PA and phoneme-grapheme correspondence (Gustafson et al, 2011;McArthur et al, 2018;Vellutino et al, 2008;Wanzek et al, 2018;Wolff, 2011;Wolff, 2016). Gustafson et al 2011 Lastly, in Wolff's study (Wolff, 2011), 9-year-old children took part in a multi-component reading intervention (PA, reading fluency and comprehension; 12 weeks for a total of 40 hr).…”
Section: Discussionsupporting
confidence: 82%
“…At T3, when Group 2 had received systematized phonics, they outperformed Group 1 in a comparable manner. This is in line with previous studies reporting positive reading outcomes for intervention methods with a primary focus on PA and phoneme-grapheme correspondence (Gustafson et al, 2011;McArthur et al, 2018;Vellutino et al, 2008;Wanzek et al, 2018;Wolff, 2011;Wolff, 2016). Gustafson et al 2011 Lastly, in Wolff's study (Wolff, 2011), 9-year-old children took part in a multi-component reading intervention (PA, reading fluency and comprehension; 12 weeks for a total of 40 hr).…”
Section: Discussionsupporting
confidence: 82%
“…With the p-value of smaller than 0.05 (p=0.001), it was deduced that there was a significant difference in accuracy score gained in the ORF assessment before and after the synthetic phonics intervention. This is in line with the past studies conducted by other researchers that had proven synthetic phonics to be indeed effective in developing the accuracy aspect of reading fluency (Torgerson, Brooks & Hall, 2006;McArthur et al, 2018;Day, 2017). In this research, reading accuracy was measured in term of percentage of words read correctly within one minute of passage reading.…”
Section: Standard Deviation T-value P-value Pre Testsupporting
confidence: 89%
“…For instance, the research conducted by Gomez (2016) proved synthetic phonics to be effective on the reading fluency of the first-grade pupils in term of rate. Meanwhile, there are also some researches which found synthetic phonics to be effective in accuracy aspect of reading fluency among young learners (Torgerson, Brooks & Hall, 2006;McArthur et al, 2018;Day, 2017).…”
Section: Synthetic Phonics In the Teaching Of Reading Fluencymentioning
confidence: 99%
“…Current evidence suggests that phonological decoding responds reliably to 'phonics' training, which teaches readers how to apply GPC rules during reading and/or phoneme-grapheme correspondence (PGC) rules during spelling. Meta-analyses have reported that phonics training has statistically significant moderate-to-large effects on word reading accuracy in poor readers for real words (d = 0.51-0.67) and for nonsense words (nonwords; d = 0.60-0.76; Ehri et al, 2001;McArthur et al, 2018). In the PRAX intervention used in this study, we use the Macquarie University Reading Clinic (MURC) Reading Gaps and Spelling Gaps programmes for the phonological decoding module of the PRAX schema (see "Methods" below; Kohnen, Banales & McArthur, 2020), as this intervention adopts an individualised and tailored approach to teaching children phonics.…”
Section: Introductionmentioning
confidence: 99%